1996
DOI: 10.1007/bf01200999
|View full text |Cite
|
Sign up to set email alerts
|

Short-term inhibition of the energy metabolism affects motility but not surface properties of sperm cells

Abstract: Centrifugal countercurrent distribution (CCCD) in aqueous two-phase systems has been proven to be a useful method to study subtle surface properties of spermatozoa. The present work shows that a short-term inhibition of the energy metabolism of sperm cells effected by incubating bovine sperm cells with KCN or ouabain, did not account for changes in the cell surface properties, as assessed either by estimation of the cell viability or by CCCD analysis. However, the short-term inhibition of energy metabolism pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…In line with the model predictions, several studies have shown that levels of different protein members of this family are lower in asthenozoospermic samples than those with normal motility [Ruiz-Pesini et al 1998;Ruiz-Pesini et al 2000;Martínez-Heredia et al 2008]. In addition, it has been observed that inhibition of complex IV results in a dramatic decrease in sperm motility [Brown 1995;Pascual et al 1996].…”
Section: Oxidative Phosphorylationsupporting
confidence: 62%
“…In line with the model predictions, several studies have shown that levels of different protein members of this family are lower in asthenozoospermic samples than those with normal motility [Ruiz-Pesini et al 1998;Ruiz-Pesini et al 2000;Martínez-Heredia et al 2008]. In addition, it has been observed that inhibition of complex IV results in a dramatic decrease in sperm motility [Brown 1995;Pascual et al 1996].…”
Section: Oxidative Phosphorylationsupporting
confidence: 62%
“…A higher affinity for the lower dextran-rich phase would indicate a decreased hydrophobicity of the acrosome-reacted sperm surface. The saccharide residues exposed to the medium as a consequence of the acrosome reaction would decrease the hydrophobicity of the sperm cells, as has already been described (Amann et al, 1993); however, these results are in disagreement with our previous report in which we had shown that loss of acrosome did not appear to significantly affect the partitioning of ram spermatozoa (Pascual et al, 1996). This contradiction could be the result of differences in the experimental conditions because, in that paper, not only had the spermatozoa been washed with Percoll gradient, but the phosphate concentration in the 2-phase system was also higher (7 mM), which increased the partition that occurred in the upper PEG-rich phase.…”
Section: Discussioncontrasting
confidence: 70%
“…This suggests that SCOT-t has novel functions in stimulating the process of germ cell differentiation and in mediating the function of sperm, as SCOT-s is defective in germ cells. Several investigators have reported the importance of mitochondrial enzymes for energy metabolism in sperm motility and function (Pascual et al, 1996;Yeung et al, 1996;Ruiz-Pesini et al, 1998). The scot-t gene product in mitochondria would play an important role in energy metabolism of haploid germ cells and in sperm that utilize ketone bodies as the energy source, which facilitates spermatid morphogenesis and sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescent staining demonstrated the mitochondrial localization of SCOT‐t protein in fixed sperm samples from both mice (Koga et al ., 2000) and humans (Tanaka et al ., 2002). These results indicated the existence of a novel metabolic system that utilized ketone bodies as an energy source for sperm motility and function (Pascual et al ., 1996; Yeung et al ., 1996; Ruiz‐Pesini et al ., 1998) and some specific roles for SCOT‐t in spermiogenesis. In the present study, we investigated the expression of both the somatic SCOT (referred to as SCOT‐s) and SCOT‐t in mouse testis in an attempt to understand the differential roles of these two enzymes.…”
Section: Introductionmentioning
confidence: 99%